Pengaruh Pengaruh Soft Skill dan Hard Skill terhadap Prestasi Kerja - Puspa Ratih; Markoni Aswan; Janusi Waliamin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The development of a company where the individual can do the work in accordance with the directions made so as not to harm the company. This study aims to determine how much influence Soft Skills and Hard Skills have on Work Performance at Pt Putra Sebakas Abadi. The variables of this study are Soft skills and Hard skills. The method used in this research is distributing questionnaires. This research is a qualitative approach research. Sources of data in this study consisted of primary data and secondary data obtained through observation and distribution of questionnaires to the respondents. The population of this study were all employees of PT Putra Sebakas Abadi, the respondents in this study were 45 samples using the saturated sample method. The analytical tool used in this study uses SPSS 22. The data analysis method used is multiple linear regression analysis. The results showed that (1) soft skills did not significantly influence work performance at Pt Putra Sebakas Abadi, (2) hard skills had a significant effect on work performance at Pt Putra Sebakas Abadi. (3) Soft skills and Hard skills simultaneously influence work performance at PT Putra Sebakas Abadi. So as to produce feedback that can be mutually accepted and given to the company so that the company benefits, it influences each other.